Assessment of the application for renewal of authorisation of ECONASE® XT (endo‐1, 4‐β‐xylanase) as a feed additive for piglets (weaned), chickens for fattening, chickens reared for laying, turkeys for fattening and turkeys reared for breeding. (7th November 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; de Lourdes Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: ECONASE ® XT is an enzyme based on endo‐1, 4‐β‐xylanase produced by a genetically modified strain of Trichoderma reesei ■■■■■. The additive is currently authorised for use in chickens for fattening or reared for laying, turkeys for fattening or reared for breeding, laying hens, weaned piglets, pigs for fattening and minor poultry species. This scientific opinion concerns the renewal of the authorisation of the additive when used in weaned piglets, chickens for fattening, chickens reared for laying, turkeys for fattening and turkeys reared for breeding. ECONASE ® XT is currently authorised in two forms, a solid and a liquid form with activities of 4, 000, 000 and 400, 000 BXU/g, respectively. The current application also comprises three new less concentrated formulations. The applicant has provided evidence that the additive currently in the market complies with the existing conditions of authorisation. The Panel could not exclude the potential presence of recombinant DNA derived from the production organism in recent batches. However, since no sequences of concern have been introduced in the production strain, the potential presence of recombinant DNA in the final product does not raise any safety concern. No new evidence has been produced that would lead the Panel to reconsider its previous conclusions on the safety of the product for target species, consumers, users and the environment under the authorised conditions of use. Therefore, the FEEDAP Panel confirms that ECONASE ® XT is safe for the target species, consumers of products from animals fed the additive and the environment. ECONASE ® XT is non‐irritant to the skin, the liquid form is non‐irritant to the eyes and is not a dermal sensitiser, but the additive in all forms should be considered a potential respiratory sensitiser. There is no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.